Lifewall : a modular emergency water storage and wellness system : an exegesis presented in partial fulfilment of the requirements for the degree of Masters of Design (198.800) at Massey University, Wellington, New Zealand - Jones, Michael Scott (Massey University, 2017)
The New Zealand Ministry of Civil Defence and Emergency Management supports and enables communities to manage when emergencies strike, and encourages preparedness across the country. The Ministry recommends a list of emergency survival items for the home, including a supply of potable water. Specifically, three litres of water per person per day for three days. The Ministry also recommends stocking enough food and water for up to two weeks in the home for prolonged emergencies. A natural disaster event such as an earthquake can disrupt mains supplied potable water. The resilience of the water network systems during and after events is vital for the response and recovery of the community. Providing safe drinking water, in the initial days after a natural disaster event is crucial to maintaining the health, well-being and resilience of isolated and affected disaster victims. Conventional approaches to supplying water in a post natural disaster event zone have been proven logistically challenging, cumbersome and costly to maintain for extended periods of time. These issues provide an opportunity for new product innovation to address the emergency water supply scenario. Lifewall, the result of this research project, seeks to ameliorate many of the issues faced in emergency potable water supply due to a natural disaster event. Lifewall has been achieved through an iterative cycle of research through design, building an understanding of the disaster scenario and the latent performance needs required by users. By taking a human centred industrial design approach, key performance features such as manual handling, usability, integration into the local environment and resilience along with desirability have been addressed. This has involved a range of methods including: ideation, computer assisted design, task analysis, physical prototyping and testing throughout the project. This heuristic design approach has led to an emergency water storage system with a modular product architecture, which maximises water resource survivability and improves utility before and after a disaster event. The Lifewall system consists of four main components: Lifewall Unibody Lifecell Lifepod BIQC (Bottle integrated quick coupler) The Lifewall system sources water from the municipal supply. It filters and stores a volume of water for emergency purposes which renews and refreshes itself. It does this through the daily use of the living space that it is connected to. In a seismic event it automatically isolates itself to protect stored water, supporting resilience in the community. During this research degree, New Zealand experienced the third biggest earthquake ever in its recorded history, a poignant reminder of the need for products of this type and design research in this area.
Keywords: Hydraulics -- Technological innovations; Storage tanks -- Design and construction; Water -- Storage -- Equipment and supplies; Survival and emergency equipment; Emergency water supply; Research Subject Categories:TECHNOLOGY